IMPLEMENTASI AKAD MURABAHAH PADA PT AMARTHA MIKRO FINTEK CABANG PRINGKUKU AREA PACITAN - Aldo Robby Pradana; Ufi Febiana (Commodity : Jurnal Perbankan dan Keuangan Islam, 2023)
PT Amartha Mikro Fintek or Amartha is a peer-to-peer financial technology company in Indonesia. Amartha is a fintech or P2P financial technology company in Indonesia. The company offers a website that connects urban financiers with rural micro and small business owners. In this financing product, Amartha has a main financing product (group loan) or the first phase of financing that uses a Murabahah contract in its contract. This study uses a descriptive qualitative approach that aims to systematically describe the research focus related to the Murabahah contract. Data analysis aims to simplify the processed data to make it easier to read. Data collection is done through observation, interviews, and documentation. From the results of his research it can be concluded that the implementation of the murabahah contract on the main financing or the first financing cycle is by the contract that is applied, namely the Murabahah contract.